2014
DOI: 10.3390/molecules19067913
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fingerprint of Italian Populations of Orchids Using Solid Phase Microextraction and Gas Chromatography Coupled with Mass Spectrometry

Abstract: Abstract:The volatile fraction of Ophrys sphegodes Mill. subsp. sphegodes, Ophrys bertolonii subsp. benacensis (Reisigl) O. Danesch, E. Danasch & Ehrend. and Neotinea tridentata (Scop.) R.M. Bateman, Pridgeon & M.W. Case, three orchid species with different pollinator attraction strategies, sampled in vivo and in situ, were evaluated by headspace solid phase microextraction coupled with gas-chromatography and mass spectrometry. The results were compared with the volatile compounds emitted by flowering plant sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…All analyses were performed according to Manzo and co-workers [46]. For Headspace Solid-Phase Microextraction (HS-SPME), the eggs were placed in a 20 mL headspace glass vial fitted with a cap equipped with a silicone/polytetrafluoroethylene septum (Supelco).…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed according to Manzo and co-workers [46]. For Headspace Solid-Phase Microextraction (HS-SPME), the eggs were placed in a 20 mL headspace glass vial fitted with a cap equipped with a silicone/polytetrafluoroethylene septum (Supelco).…”
Section: Methodsmentioning
confidence: 99%
“…A high percentage of saturated hydrocarbons has been detected in the volatile fraction of all the four Italian sympatric orchid species. The presence of saturated hydrocarbons in higher percentage with respect to other published research [28] is probably due to the different extraction procedures like solid-phase microextraction that work at lower extraction temperatures. In detail, a series of homologous linear chain compounds ranged from C 9 to C 29 have been reported for all the terrestrial and epiphytic orchids.…”
Section: Discussionmentioning
confidence: 69%
“…The SPME device was fixed besides the glass funnel, with the hollow SPME needle stuck through the aluminum foil, exposing the fiber close to the flower. Through the study of scent production by Petunia Mitchell flowers, Verdonk et al demonstrated that SPME coupled to GC-MS is an outstanding tool to measure the volatile production by flowers in vivo, and the similar result was confirmed by Manzo et al [71]. Song et al analyzed the VOCs emitted from living daffodil flowers with in vivo SPME by the similar device [72].…”
Section: Flowersmentioning
confidence: 60%